2022
DOI: 10.1101/2022.03.08.22272062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Safety and immunogenicity of a hybrid-type vaccine booster in BBIBP-CorV recipients: a randomized controlled phase 2 trial

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with immune escape ability raises the urgent need for developing cross-neutralizing vaccines against the virus. NVSI-06-08 is a potential broad-spectrum recombinant COVID-19 vaccine that integrates the antigens from multiple SARS-CoV-2 strains into a single immunogen. Here, we evaluated the safety and immunogenicity of NVSI-06-08 as a heterologous booster dose in adults previously vaccinated with the inactivated vaccine BBIB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 121 studies under full-text review, 98 studies were excluded. Eventually, 23 studies (including 13 published articles and 10 preprints) were included in this meta-analysis based on the inclusion criteria [ 14 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The literature retrieval flow chart is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported the long-term immune persistence after the priming full-schedule vaccination and the safety and immunogenicity of booster dose with different technical platform COVID19 vaccines in different population [11][12][13][14][15][16][17][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the homologous booster dose with inactivated vaccines led to a strangely rebound in neutralizing immune response against SARS-CoV-2. A non-peer-reviewed study [21] found the GMT of neutralizing antibodies was improved 1.04-3.87-fold on day 30 after a booster dose of BBIBP-CorV vaccine compared to the 28 days after the second dose. Similarly, one study [14] of 353 healthy adult participants who administered with a two-shot regiment (28 days apart) BBIBP-CorV vaccine (month 1) and a booster dose 7 months later, the GMT increased 4.5 times, compared to GMT of month 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations